Quem tem medo de quem nas cidades de hoje? Políticas de segurança pública em tempos neoliberais - Sonia Maria Taddei Ferraz; Clara Braga de Britto Pereira; Leticia Lyra Acioly; Nicolle Peres Cardoso (Les Cahiers ALHIM)
These text updates reflections about the frame of private strategies of security against the violence in the city of Rio de Janeiro, having like underpinning the new neoliberal processes of capitalist acumulation Which has redesingning the carioca paisage. It’s the fear of the violence that gives city aspects and conformations wich simbolize with clarity the class conflicts. The social-economics disequality is represented by distint forms of being and dwell in the polarized citys by the Double exclusion: the self-exclusion of elites in the neighborhoods of high income – hiring private security of all kinds – and the exclusion of peripheral and miserable poor without acess to home and the public spaces. In the last years the neoliberais strategies brought to the camp of public politics of security the public-private partnerships by the glamorous Operação Segurança Presente by the copy of food-trucks stetic. With the promisse of combat to the violence, the new politics maintained the security ideary and encourages the security marketplace, delighting and instituting new urban territories like turism and consumption arenas, emptied of conflict, redesigning a paisage apparently safety, colorful, happy and festive, as if the consumption was democrated and the life was fair for all.